New records of culicidae (Diptera) in agricultural oases of San Juan Province, Argentina - Díaz Nieto, Leonardo Martín (2020)
We report eight new Culicidae records from San Juan province, Argentina: Anopheles argyritarsis Robineau-Desvoidy, 1827; Anopheles neomaculipalpus Curry, 1931; Culex acharistus Root, 1927; Culex apicinus Philippi, 1965; Culex maxi Dyar, 1928; Culex quinquefasciatus Say, 1823; Culex saltanensis Dyar, 1928; and Haemagogus spegazzinii Brethes, 1912. The geographic distribution of Aedes aegypti (Linnaeus, 1762), Aedes albifasciatus (Macquart, 1838), Anopheles pseudopunctipennis Theobald, 1901, Culex pipiens Linneaus, 1758, Culex tramazayguesi Duret, 1954, and Psorophora cyanescens (Coquillet, 1902) is extended. Data on collection localities, types of breeding sites and health importance are also presented.